Effect of Educational Program on the Burden of Family Caregivers of Hemodialysis Patients - Mansoureh Ashghali Farahani; Golnar Ghane; Naime Sydfatemi; Hamid Hagani (Mashhad University of Medical Sciences, 2016)
Background: Studies suggest that family caregivers of hemodialysis patients experience a high level of burden, which could lead to numerous physical and psychological problems. Despite the need for adequate training and support, these caregivers are mostly neglected, and few studies have been performed in this regard. Aim: to evaluate the effect of educational programs on the home care of hemodialysis patients and burden of their family caregivers. Method: This randomized controlled clinical trial was conducted on 76 caregivers of hemodialysis patients referred to Shahid Hasheminejad Hemodialysis Center of Tehran, Iran in 2015. Subjects were divided into two groups of intervention and control (n=38). The intervention group received four training sessions on the home care of hemodialysis patients for two weeks, and the control group received routine care. Data were collected using the Caregiver Burden Inventory (CBI) at the beginning and six weeks after the intervention. Data analysis was performed in SPSS V.21 using Chi-square, Fisher's exact test, independent and paired T-test, and Mann-Whitney U test. Results: In this study, no significant difference was observed between the two groups in terms of demographic characteristics. At the baseline, mean score of caregiver burden in the intervention and control groups was 88.5±11.7 and 84.9±15.1, respectively, and no significant difference was observed between the groups in this regard (P=0.30). Six weeks after the intervention, the results of independent T-test revealed a significant difference between the mean scores of caregiver burden in the intervention (58.7±6.6) and control groups (87.8±11.7) (P